1964
DOI: 10.1085/jgp.48.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between Alkali Metal Cations by Yeast

Abstract: Extracellular pH markedly influences the ability of yeast cells to discriminate between K+ and Na+, with K+ favored to a greater degree at low pH. Studies of the kinetics of uptake of individual alkali metal cations by fermenting yeast indicate three zones relative to pH. Between pH 6 and 8, H + has no effect. Below pH 4, H + competitively inhibits the transport of each cation. Between pH 4 and 6, H+ acts kinetically as a predominantly non-competitive inhibitor. Both effects can be reversed by increasing the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
59
1

Year Published

1970
1970
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 6 publications
11
59
1
Order By: Relevance
“…Most information is available for K"^ since this ion is preferentially taken up by the monovalent cation transport system (Conway & Duggan, 1958;Borst-Pauwels, 1981). Early work described this system as 'the physiological Kĉ arrier' although other monovalent ions including Rb"^, Na^, Cs^, Li^ and NH4^ may be transported with lower affinities (Jennings, Hooper & Rothstein, 1958;Armstrong, 1964). Ca^+ and Mg'+ can also be taken up via the K^ transport system though the affinity for these cations is very low (Borst-Pauwels, 1981).…”
Section: Transport Of Toxic Metal Cations*mentioning
confidence: 99%
See 1 more Smart Citation
“…Most information is available for K"^ since this ion is preferentially taken up by the monovalent cation transport system (Conway & Duggan, 1958;Borst-Pauwels, 1981). Early work described this system as 'the physiological Kĉ arrier' although other monovalent ions including Rb"^, Na^, Cs^, Li^ and NH4^ may be transported with lower affinities (Jennings, Hooper & Rothstein, 1958;Armstrong, 1964). Ca^+ and Mg'+ can also be taken up via the K^ transport system though the affinity for these cations is very low (Borst-Pauwels, 1981).…”
Section: Transport Of Toxic Metal Cations*mentioning
confidence: 99%
“…As the pH is progressively decreased below pH 7-0, the selectivity for K"^ and Rb^ over all other ions is increased. In a 1 :1 mixture of K"^ and Na^ at pH 4-0, the combined effects of competitive inhibition of K"" against Na"^ and the effect of low pH against Na^ mean that Na"^ uptake becomes negligible (Armstrong & Rothstein, 1964). It should also be noted that the kinetics of Kt ransport can alter depending on growth and assay conditions.…”
Section: Transport Of Toxic Metal Cations*mentioning
confidence: 99%
“…The significance of increased glycerol production is also obscure. Its production could be a result of the activation of certain enzymes on the pathway leading to glycerol by NaCl (Schoeffeniels, 1969); alternatively, it might be a byproduct of increased organic acid production necessary for NAD/NADH, regulation (a fall in pH value would be advantageous as it decreases the velocity of Na+ uptake; Armstrong & Rothstein, 1964). It is, however, difficult to explain why the increased production of glycerol expressed itself primarily as a maintenance effect.…”
Section: (5)mentioning
confidence: 99%
“…The K+ uptake system of S. cerevisiae also mediates the uptakes of Na+ and Li', although these cations show much higher Kms than K+ and Rb+, especially in K+-starved cells (1,12). Experiments with Na+ and Li+ similar to those carried out with Rb+ showed that their influxes were also stimulated by glucose (e.g., the Vm.s of Li+ influx in the absence and in the presence of glucose were 1 and 9 nmol mg1 min1, respectively).…”
mentioning
confidence: 99%